(untitled) (Marketing Journal, 2025)
This article explores the scientific and theoretical aspects of the effective use of working capital in enterprises. Additionally, the working capital status and the dynamics of structural changes at “Maxam Chirchiq” JSC have been analyzed as the object of the study. Problems related to the volume and efficient utilization of working capital in enterprises have been identified, and proposals aimed at addressing these issues have been developed.